Maxillary sinus - A tool for sex determination in the Nepalese population - Singh, Pankaj Kumar; Paudel, Ram Chandra; Menezes, Ritesh G; Khanal, Kishor (Journal of Kathmandu Medical College, 2019)
Background: In forensic science, skeletal examination is often done with primary focus on identification. Complete identification is a rare event in this type of examination. However, anthropological identification can be done in skeletal examination. Skull is the second best for determination of sex next to pelvis. Maxillary sinuses are paranasal sinuses, and a feature for sexual dimorphism which remains intact in partially charred. The study of maxillary sinus is best done on Computed Tomography.Objectives: The primary objective of this study is to evaluate bilateral maxillary sinus for sexual dimorphism using Computed Tomography.Methodology: A total of 104 CT head cases were studied of which 52 were male and 52 female. The anterior posterior length, transverse width and height of bilateral maxillary sinus were measured in male and female through their DICOM images using inbuilt electronic calliper. Descriptive analysis for mean, paired t test to compare right and left maxillary sinus in both male and female, and student t test for compare male and female were used for analysing the value measured and calculated.Results: Male maxillary sinus (Right 12.76±4.62 & Left 12.39±3.81) was found be to larger than that of female (Right 12.16±4.78 & Left 11.80±4.49). Right and left maxillary sinus of both the sexes showed no significant difference when paired t test was used. Using independent t-test showed no sexual dimorphism between the two sexes.Conclusion: Maxillary sinus is not good tool for sex determination in Nepalese population. However further studies could be done on larger population sample, as smaller sample size could be the limitation of this study.